Valorization of microwave-assisted H3PO4-activated plantain (Musa paradisiacal L) leaf biochar for malachite green sequestration: models and mechanism of adsorption - Jamiu Mosebolatan Jabar; Matthew Ayorinde Adebayo; Yisau Adelaja Odusote; Murat Yılmaz; Selvasembian Rangabhashiyam (Results in Engineering, 2023)
Utilization of synthetic dyes in different sectors has been identified as one of the major sources of environmental degradation; as a result, removal of their remnants from the industrial effluent is highly encouraged for conserving our environment. In this study, the synthesized plantain leaf biochar (PLB) was used for adsorbing synthetic malachite green (MG). The synthesized PLB was characterized through pHpzc, BET, XRD, SEM and FTIR spectrometry. The sequestration of MG onto PLB confirmed by FTIR and SEM was optimized by varying the adsorption parameters. The BET surface area (986.35 m2/g) and average pore diameter (44.13 Å) showcased PLB as an efficient mesoporous biochar capable of adsorbing MG (>99%) at optimum conditions of pH (8.0), initial MG concentration (50 mg/L), adsorbent dosage (0.2 g/L), contact time (80 min) and temperature of 301 K. Redlich-Peterson and Avrami fractional model best fitted the adsorption isotherm and kinetic model, respectively. ΔGo and ΔHo being negative confirmed the feasibility and exothermic nature of the adsorption process. The outstanding regeneration (>97%) of PLB after the fifth regeneration cycle established PLB as a potential sustainable green adsorbent for future industrial wastewater treatment.